Pengaruh Keragaman Produk, Harga, Promosi, Lokasi, Dan Pelayanan Terhadap Keputusan Pembelian (Studi Kasus Konsumen Minimarket Swalayan 89 Kota Probolinggo) - Nida Aulia Amatullah; Rois Arifin; Rahmawati Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of product diversity, price, promotion, location and service on purchasing decisions for consumers of Supermarket Minimarket 89 Probolinggo City. The sample in this study amounted to 120 respondents who were consumers of 89 supermarkets in Probolinggo City. The sampling technique used is purposive sampling. The data used in the study used primary and secondary data. The method used is data analysis by using validity, reliability, normality, multicollinearity test, heteroscedasticity test, multiple linear regression analysis test, f test, t test and coefficient of determination with the IBM statistical SPSS version 25 program. With research results showing that simultaneously each product diversity, price, location promotion, and service equally affect purchasing decisions, while partially variable product diversity, price, promotion, and location have a significant effect on purchasing decisions at Supermarket Minimarket 89 Probolinggo City Keywords: Product Diversity, Price, Promotion, Location, Location, Purchase Decision Keywords : Purchase Decision, Product Diversity, Price, Promotion, Location and Service